2020
DOI: 10.1080/19415257.2020.1712615
|View full text |Cite
|
Sign up to set email alerts
|

Teacher educators reflecting on case-based teaching – a collective self-study

Abstract: The current study is a collective self-study on how we as 15 teacher educators at a university in Norway tried to improve our teaching through working with cases with the aim of better supporting student teachers in making links between theory and practice. We wanted to address the common criticism in teacher education concerning a perceived gap between practice and theory.Our presupposition was that one way to prepare student teachers for work and bring together theoretical and practical knowledge would be th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
0
11
0
6
Order By: Relevance
“…In a previous study we found that providing student teachers with guidelines and time improved the quality of their work with cases (Ulvik et al 2020). This time we did not present any expectations for the work but assumed that the student teachers understood our implicit expectations based on their previous work with cases, albeit in a different context.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In a previous study we found that providing student teachers with guidelines and time improved the quality of their work with cases (Ulvik et al 2020). This time we did not present any expectations for the work but assumed that the student teachers understood our implicit expectations based on their previous work with cases, albeit in a different context.…”
Section: Discussionmentioning
confidence: 76%
“…Cases are a crucial part of the current programme. They are used in plenary lectures, either as illustrations or for discussion in summary report groups, and they are discussed in seminars (see Ulvik et al 2020). Furthermore, the students' exam the first semester consists of presenting a case from the first placement and analyse it with the help of theory.…”
Section: Context and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the case is understood as a realistic narrative from classrooms and schools. The research literature provides several positive outcomes for case-based teaching (Ulvik et al 2020). In the last decades, educationists have argued for case-based teacher education mainly due to the fact that facing dilemmas from practice can prepare the students for how to diagnose, make decisions and how to act (Heitzmann 2008;Merseth 1996;Sato and Rogers 2010;Shulman 2004).…”
Section: Casesmentioning
confidence: 99%
“…Combining reading theory with writing their own cases and sharing them with their peers can help student teachers to connect research and practice (Hammerness, Darling-Hammond, and Shulman 2002). Writing about their own critical incidents may help students to learn from their experiences (Ulvik et al 2020). Findings from Levin's study (2002) of students who wrote their cases based on critical incidents show that writing about their own dilemmas allowed students to resolve their problems, which again influenced the perception of their roles and relationships in the classroom in a positive way.…”
Section: Casesmentioning
confidence: 99%